2015
DOI: 10.1021/acs.cgd.5b01240
|View full text |Cite
|
Sign up to set email alerts
|

Furosemide Cocrystals with Pyridines: An Interesting Case of Color Cocrystal Polymorphism

Abstract: Furosemide (FS), a loop diuretic drug commonly used for the treatment of hypertension and edema, exhibited color cocrystal polymorphism with coformer 4,4′bipyridine (4BPY) in the stoichiometry 2:1, albeit both the API and the cocrystal former are colorless. Crystallization from ethanol, isopropanol, ethanol−water (v/v, 1/1) mixture, and acetonitrile yielded pale yellow (form 1I, thin needles) and orange (form 1II, blocks) cocrystals concomitantly. Needles appeared from solution within a day, while the blocks w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 36 publications
3
35
0
Order By: Relevance
“…FUROS has two strong hydrogen-bonding functional groups (COOH and SO 2 NH 2 ) for crystal engineering. Binary cocrystals of FUROS with acetamide, picolinamide, nicotinamide, isonicotinamide, anthranilamide, toluamide, isoniazid, piperazine, tetramethylpyrazine, pyrazine, picolinic acid, p-aminobenzoic acid, caffeine, urea, theophylline, adenine, cytosine, bipyridines, amino pyridines, pentoxifylline and pyridine N-oxides have been reported (Goud et al, 2012;Harriss et al, 2014;Sangtani et al, 2015;Banik et al, 2016;Stepanovs & Mishnev, 2012).…”
Section: Furosemide Cocrystalsmentioning
confidence: 99%
“…FUROS has two strong hydrogen-bonding functional groups (COOH and SO 2 NH 2 ) for crystal engineering. Binary cocrystals of FUROS with acetamide, picolinamide, nicotinamide, isonicotinamide, anthranilamide, toluamide, isoniazid, piperazine, tetramethylpyrazine, pyrazine, picolinic acid, p-aminobenzoic acid, caffeine, urea, theophylline, adenine, cytosine, bipyridines, amino pyridines, pentoxifylline and pyridine N-oxides have been reported (Goud et al, 2012;Harriss et al, 2014;Sangtani et al, 2015;Banik et al, 2016;Stepanovs & Mishnev, 2012).…”
Section: Furosemide Cocrystalsmentioning
confidence: 99%
“…A more challenging aspect is to quantify nanocrystals in an amorphous material. Scherrer broadening (broadening of the diffraction peaks due to a reduction in crystallite size) may reduce the diffracted intensity for a crystalline material such that it becomes [205] √ (ATR) √ √ √ Nitrofurantoin cocrystal solvate, hydrates, salts [206] √ √ √ √ √ Nitrofurantoin cocrystal hydrate [126] √ √ √ √ √ Caffeine cocrystal polymorph, hydrate and solvates [116][207] √ √ √ √ Salicylic acid cocrystal polymorphs [118] √ √ Felodipine cocrystal polymorph [115] √ √ √ Benzoic acid cocrystal polymorph [208] √ √ √ Glycine cocrystal polymorph [166] √ √ Vanillic acid cocrystal hydrate [125] √ √ √ √ Agomelatin cocrystal polymorph [209] √ √ √ √ Diclofenac cocrystal polymorph hydrate [104] √ √ (VT) √ √ Nicotinamide cocrystal polymorph [210] √ √ √ √ √ Phenazine cocrystal polymorph and solvate [105] √…”
Section: X-ray Diffraction Techniquesmentioning
confidence: 99%
“…Several reports are available in the literature where the role of hydrogen bonding in altering physiochemical properties of an API has been reported [ 15 , 95 ]. However, very limited reports are available in the literature where Π…Π stacking interactions were utilized for modulating the physiochemical properties of pharmaceutical cocrystals [ 17 , 257 , 258 ].…”
Section: Influence Of Intermolecular Interactions On Cocrystallizamentioning
confidence: 99%
“…Sangtani et al [ 257 ] observed concomitant color polymorphism in Furosemide-4,4′-bipyridine (2:1) cocrystals (Forms I and II). Form I cocrystal appeared as pale yellow needles whereas form II cocrystal appeared as orange blocks [ 257 ]. Form I cocrystal was observed to crystallize at faster rate and with higher yield than the form II cocrystal.…”
Section: Influence Of Intermolecular Interactions On Cocrystallizamentioning
confidence: 99%
See 1 more Smart Citation